Document Analysis on Self-Care Skills Education for 5-6 Year - Old Children and Research Orientations - Duong, Thị Kim Oanh; Pham, Thị Mỹ Nữ (Journal of Technical Education Science, 2023)
Pre-school education is the first level in the national education system and the foundation for further education. The age of 5-6 is an important turning point for children to prepare for first grade. Self-care skills help children get familiar with daily activities, know how to handle problems, become confident and easily get along with friends, build good relationships with those around them, and be independent in life This article presents 3 main research directions on educating self-care skills for 5-6 year-old children, including (1) Concepts of self-care skills and the meaning of self-care skill education to the development of 5-6 year - old children; (2) Defferent types of self-care skills and self-care skills scale for 5 - 6 year - old children; (3) Education methods of self-care skills for 5 - 6 year-old children and factors affecting on the formation of self-care skills of 5 - 6 year-old children. In addition, the article also identifies gaps in research on self-care education for 5-6 year olds in Vietnam and proposing research orientations for self-care education for 5-6 year olds according to child-centered education perspective to meet the requirement of implementing the semina plan named “Building a child-centered preschool” in the 2021-2025 period of the Ministry of Education and Training (2021).